2005
DOI: 10.1016/j.jcat.2004.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Steam reforming of methanol over Cu/ZrO/CeO catalysts: a kinetic study

Abstract: Steam reforming of methanol (SRM) was investigated over Cu/ZrO 2 /CeO 2 (CZC) catalysts prepared via a novel synthetic method based on coprecipitation and polymer templating. Structural characterization of the samples was performed by N 2 adsorption-desorption, N 2 O decomposition, and X-ray diffraction. The variation of the Cu loading resulted in an increased Cu crystallite size and a decreased specific surface area of the active particles. Catalytic investigations were carried out in a fixed bed reactor at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 49 publications
(165 reference statements)
4
74
0
Order By: Relevance
“…7,33 Different reaction mechanisms have been reported in literature which differ in the CO formation step: some of them consider that CO is a primary product formed from methanol decomposition (MD) followed by WGS; 34 others suggest that CO is a secondary product formed from reverse WGS 5,6 and those where the three reactions (SRM, WGS, MD) are included into the mechanism. 35 In Figure 7, methanol conversion as a function of W/F MeOH is illustrated. The values at 300 °C correspond to 400 min in reaction.…”
Section: -26mentioning
confidence: 99%
See 1 more Smart Citation
“…7,33 Different reaction mechanisms have been reported in literature which differ in the CO formation step: some of them consider that CO is a primary product formed from methanol decomposition (MD) followed by WGS; 34 others suggest that CO is a secondary product formed from reverse WGS 5,6 and those where the three reactions (SRM, WGS, MD) are included into the mechanism. 35 In Figure 7, methanol conversion as a function of W/F MeOH is illustrated. The values at 300 °C correspond to 400 min in reaction.…”
Section: -26mentioning
confidence: 99%
“…This value is near data in literature. 6,35,36 Purnama et al 6 assuming a scheme of SRM and r-WGS reactions have reported Ea = 76 kJ mol -1 over a commercial CuO/ZnO/Al 2 O 3 catalyst ; and Mastalir et al 35 have informed activation energy between 109.2 and 60.7 kJ mol -1 depending on Cu/ZrO 2 /CeO 2 catalyst composition. These authors have assumed three reactions to describe the mechanism: SRM, r-WGS and MD.…”
Section: -26mentioning
confidence: 99%
“…They have studied the effect of delayed time on stream MSR behavior by continuing the process for a long period as high as 16 days. This treatment revealed the decrease in activity from ~35% to ~17% up to 9 days [7]. The coprecipitation made CuO/ZnO/ CeO2eZrO2 catalyst is shown to exhibit greater activity and long term stability and the CeO2eZrO2 (50:50) support has a greater promotional effect than pure CeO2, ZrO2 and Al2O3 [29].…”
Section: Discussionmentioning
confidence: 94%
“…The decrease in activity during long term tests is a general observation for this kind of catalytic systems [7,23,25,29]. To investigate in detail the possibility of activity recovery and the catalyst reuse after an intermediate oxidation step, we carried out regeneration tests as described in the experimental section.…”
Section: Msr Activity Of Aged and Regenerated Catalystsmentioning
confidence: 99%
See 1 more Smart Citation